Chinese Herbal Medicines and Active Metabolites: Potential Antioxidant Treatments for Atherosclerosis - Song, Luxia; Zhang, Jie; Lai, Runmin; Li, Qiuyi; Ju, Jianqing; Xu, Hao (Frontiers in Pharmacology, 2021)
Atherosclerosis is a complex chronic disease that occurs in the arterial wall. Oxidative stress plays a crucial role in the occurrence and progression of atherosclerotic plaques. The dominance of oxidative stress over anti-oxidative capacity generates excess reactive oxygen species, leading to dysfunctions of the endothelium and accelerating atherosclerotic plaque progression. Studies showed that Chinese herbal medicines and traditional Chinese medicine (TCM) might regulate oxidative stress; they have already been used to treat diseases related to atherosclerosis, including stroke and myocardial infarction. This review will summarize the mechanisms of oxidative stress in atherosclerosis and discuss studies of Chinese herbal medicines and TCM preparations treating atherosclerosis, aiming to increase understanding of TCM and stimulate research for new drugs to treat diseases associated with oxidative stress.